Analisis Biaya Lingkungan untuk Penyusunan Biaya Pengolahan Limbah Bahan Berbahaya Dan Beracun (B3) pada PT XYZ - Rianti Pramesti Putri; Mia Rosmiati (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
With the rapid development of the industry, it is not in line with the handling of waste generated by industrial activities. There are still many companies that still ignore the importance of waste management, especially those classified as Hazardous and Toxic Waste (B3). Traditionally environmental costs are hidden in general accounting for costs. Meanwhile, environmental management accounting will calculate the cost of waste as processing plus the cost of purchasing raw materials. Therefore, the aim of this study is to analyze the application of environmental costs to urban transport projects and create a special budget for B3 waste management costs. This type of research is quantitative qualitative research with descriptive methods. The data collection methods used in this study were interviews and documentation. The results of this study indicate that the urban transport project has not implemented environmental management accounting. Environmental costs are included in overhead costs which result in environmental costs, especially in the management of hazardous and toxic waste (B3) which is a hidden cost.